GAMIFICATION IN ENGLISH LANGUAGE TEACHING: ENHANCING STUDENT MOTIVATION AND COMMUNICATIVE COMPETENCE IN HIGHER EDUCATION (International journal of artificial intelligence, 2026)
Gamification has become one of the most innovative and effective approaches in modern English language teaching. The integration of game elements into educational environments increases learner motivation, engagement, and communicative interaction. This article examines the pedagogical impact of gamification on English language teaching in higher education institutions. The study analyzes the use of digital platforms, interactive applications, and game-based activities that support vocabulary acquisition, speaking development, collaborative learning, and learner autonomy. Particular attention is given to the role of gamification in improving communicative competence among university students. The findings indicate that gamified learning environments positively influence students’ academic performance, participation, and motivation when integrated within appropriate pedagogical frameworks.